Meta-analysis reveals contrasting effects of biodegradable and conventional microplastics on earthworm fitness, physiology, and gut microbiota - Hesen Zhong; Jerome Mathieu; Chengshuai Liu; Patrick Lavelle; Jun Dai; Ying Lu; Chi Zhang (Soil Biology and Biochemistry, 2026)

Exposure risk of alcids to marine vessel-associated oil pollution in Western Canada - Patrick D. O'Hara; Sonya Pastran; Douglas F. Bertram; Alexandra King; Mathieu Bourbonnais; Paul Barrett; Laurie Wilson; Ken H. Morgan; Caroline H. Fox; Gary W. Kaiser; Vivian Pattison; Leh Smallshaw; et al. (Science of The Total Environment, 2026)

Advanced strategies for discrete simulations with three-dimensional R-shapes in rockable framework - Vincent Richefeu; Gaël Combe; Lhassan Amarsid; Raphaël Prat; Jean-Mathieu Vanson; Saied Nezamabadi; Patrick Mutabaruka; Jean-Yves Delenne; Farhang Radjaï (Computer Physics Communications, 2026)

Internal handling, shell accumulation and effects of cobalt on the gastropod Ampullaceana balthica - Maëva Marimoutou; Gilles Bareille; Mathieu Milhe-Poutingon; Clémentine Gelber; Patrick Baldoni-Andrey; Nicholas Bagger Gurieff; Hélène Tabouret; Sandra Mounicou; Séverine Le Faucheur (Aquatic Toxicology, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Random mutagenesis using cold atmospheric plasma to produce mutant microalgae for hyper-recovery of rare earth elements from mining materials - Phong H.N. Vo; Mikael Kim; Unnikrishnan Kuzhiumparambil; Cora Hinkley; Jungmi Hong; Tianqi Zhang; Mathieu Pernice; Patrick J. Cullen; Peter J. Ralph (Chemical Engineering Journal, 2025)

Unravelling the magmatic and hydrothermal evolution of rare-metal granites through apatite geochemistry and geochronology: The Variscan Beauvoir granite (French Massif Central) - Océane Rocher; Christophe Ballouard; Antonin Richard; Loïs Monnier; Patrick Carr; Oscar Laurent; Yanis Khebabza; Andreï Lecomte; Nordine Bouden; Johan Villeneuve; Benjamin Barré; Patrick Fullenwarth; et al. (Chemical Geology, 2024)

Cobalt effects on prokaryotic communities of river biofilms: Impact on their colonization kinetics, structure and functions - Sarah Gourgues; Marisol Goñi-Urriza; Mathieu Milhe-Poutingon; Patrick Baldoni-Andrey; Nicholas Bagger Gurieff; Clémentine Gelber; Séverine Le Faucheur (Science of The Total Environment, 2024)

Growing maize while biological remediating a multiple metal-contaminated soil: a promising solution with the hyperaccumulator plant Sedum alfredii and the earthworm Amynthas morrisi - Chi Zhang; Hesen Zhong; Jerome Mathieu; Bo Zhou; Jun Dai; Mikael Motelica-Heino; Patrick Lavelle (Plant and Soil, 2024)

Complementary classifications of aeolian dunes based on morphology, dynamics, and fluid mechanics - Sylvain Courrech du Pont; David M. Rubin; Clément Narteau; Mathieu G.A. Lapôtre; Mackenzie Day; Philippe Claudin; Ian Livingstone; Matt W. Telfer; Jani Radebaugh; Cyril Gadal; Andrew Gunn; Patrick A. Hesp; et al. (Earth-Science Reviews, 2024)

New sensitive tools to characterize meta-metabolome response to short- and long-term cobalt exposure in dynamic river biofilm communities - Simon Colas; Benjamin Marie; Soizic Morin; Mathieu Milhe-Poutingon; Pierre Foucault; Siann Chalvin; Clémentine Gelber; Patrick Baldoni-Andrey; Nicholas Gurieff; Claude Fortin; Séverine Le Faucheur (Science of The Total Environment, 2024)

Correction factors for large-scale greenhouse gas assessment from pulp and paper mill sludge landfill sites - Ranieri Ribeiro Paula; Mathieu Cusson; Normand Bertrand; Sylvie Bouchard; Martin H. Chantigny; Julie Lemieux; Emna Marouani; Claude Villeneuve; Patrick Faubert (Waste Management, 2024)

Adaptive probabilistic modelling to support decision-making in the event of accidental atmospheric releases - Maéva Caillat; Valentin Pibernus; Sylvain Girard; Mathieu Ribatet; Patrick Armand; Christophe Duchenne (Atmospheric Environment, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

WildHealthNet: Supporting the development of sustainable wildlife health surveillance networks in Southeast Asia - Mathieu Pruvot; Emily Denstedt; Alice Latinne; Alice Porco; Diego Montecino-Latorre; Kongsy Khammavong; Phonesavanh Milavong; Souchinda Phouangsouvanh; Manoly Sisavanh; Nguyen Thi Thanh Nga; Pham Thi Bich Ngoc; Vo Duy Thanh; et al. (Science of The Total Environment, 2023)

Field scale plant water relation of maize (Zea mays) under drought – impact of root hairs and soil texture - Helena Jorda; Mutez A. Ahmed; Mathieu Javaux; Andrea Carminati; Patrick Duddek; Doris Vetterlein; Jan Vanderborght (Plant and Soil, 2022)
Background and aims Impact of drought on crop growth depends on soil and root hydraulic properties that determine the access of plant roots to soil water. Root hairs may increase the accessible water pool but their effect depends on soil hydraulic properties and adaptions of root systems to drought. These adaptions are difficult to investigate in pot experiments that focus on juvenile plants. Methods A wild-type and its root hairless mutant maize ( Zea mays ) were grown in the field in loam and sand substrates during two growing seasons with a large precipitation deficit. A comprehensive dataset of soil and plant properties and monitored variables were collected and interpreted using simulations with a mechanistic root water uptake model. Results Total crop water use was similar in both soils and for both genotypes whereas shoot biomass was larger for the wild type than for the hairless mutant and did not differ between soils. Total final root length was larger in sand than in loam but did not differ between genotypes. Simulations showed that root systems of both genotypes and in both soils extracted all plant available soil water, which was similar for sand and loam, at a potential rate. Leaf water potentials were overestimated by the model, especially for the hairless mutant in sand substrate because the water potential drop in the rhizosphere was not considered. Conclusions A direct effect of root hairs on water uptake was not observed but root hairs might influence leaf water potential dependent growth.

Root hairs matter at field scale for maize shoot growth and nutrient uptake, but root trait plasticity is primarily triggered by texture and drought - Doris Vetterlein; Maxime Phalempin; Eva Lippold; Steffen Schlüter; Susanne Schreiter; Mutez A. Ahmed; Andrea Carminati; Patrick Duddek; Helena Jorda; Gerd Patrick Bienert; Manuela Desiree Bienert; Mika Tarkka; et al. (Plant and Soil, 2022)
Aims Root hairs are important for uptake, especially for nutrients with low mobility in soils with high sorption capacity. Mutants with defective root hairs are expected to have lower nutrient uptake, unless they compensate with more root growth. Since root hairs can also contribute to the plant's water uptake their importance could change over the course of a growing season. It was our objective to investigate the role of root hairs under field conditions. Methods The root hair mutant rth3 of Zea mays and the corresponding wild-type were grown for two years under field conditions on sand and loam. Results Shoot growth and P and K uptake of the plants were promoted by the presence of hairs at all growth stages. Differences between genotypes were greater on loam than on sand until tassel emergence, presumably as additional exploitation by hairs is more relevant in loam. Compensation for the absence of root hairs by increased root growth was not observed in absolute terms. The root to shoot ratio was higher for rth3 than for wild-type. Root traits showed high plasticity in response to texture, the most salient being a greater mean root diameter in sand, irrespective of genotype. The mechanism causing the increase in mean root diameter is still unknown. Root length density was higher in sand, which can be explained by a greater need for exploration than exploitation in this substrate. Conclusion The role of hairs for nutrient uptake could be confirmed under field conditions. The large impact of texture on root growth and consequences for carbon balance require further investigations.

The Geotouristic Project “the Geological Adventure” to the Rescue of an Iconic World Heritage Geosite, the Ammonites Slab of Digne-les-Bains (National Geological Nature Reserve of Haute-Provence and Unesco Global Geopark, France) - Didier Bert; Violaine Bousquet; Myette Guiomar; Francesco Bariani; Jean-Claude Hippolyte; Philippe Bromblet; Jean-Luc Garciaz; Jules Fleury; Patrick Mathieu; Jean-Simon Pagès; Pierre Tardieu; Maud Dupuis-Caillot; et al. (Geoheritage, 2022)

Soil macroinvertebrate communities: A world‐wide assessment - Patrick Lavelle; Jérôme Mathieu; Alister Spain; George Brown; Carlos Fragoso; Emmanuel Lapied; Adriana De Aquino; Isabelle Barois; Edmundo Barrios; Maria Eleusa Barros; Jose Camilo Bedano; Eric Blanchart; et al. (Global Ecology and Biogeography, 2022)
Aim Macroinvertebrates comprise a highly diverse set of taxa with great potential as indicators of soil quality. Communities were sampled at 3,694 sites distributed world‐wide. We aimed to analyse the patterns of abundance, composition and network characteristics and their relationships to latitude, mean annual temperature and rainfall, land cover, soil texture and agricultural practices. Location Sites are distributed in 41 countries, ranging from 55° S to 57° N latitude, from 0 to 4,000 m in elevation, with annual rainfall ranging from 500 to >3,000 mm and mean temperatures of 5–32°C. Time period 1980–2018. Major taxa studied All soil macroinvertebrates: Haplotaxida; Coleoptera; Formicidae; Arachnida; Chilopoda; Diplopoda; Diptera; Isoptera; Isopoda; Homoptera; Hemiptera; Gastropoda; Blattaria; Orthoptera; Lepidoptera; Dermaptera; and “others”. Methods Standard ISO 23611‐5 sampling protocol was applied at all sites. Data treatment used a set of multivariate analyses, principal components analysis (PCA) on macrofauna data transformed by Hellinger’s method, multiple correspondence analysis for environmental data (latitude, elevation, temperature and average annual rainfall, type of vegetation cover) transformed into discrete classes, coinertia analysis to compare these two data sets, and bias‐corrected and accelerated bootstrap tests to evaluate the part of the variance of the macrofauna data attributable to each of the environmental factors. Network analysis was performed. Each pairwise association of taxonomic units was tested against a null model considering local and regional scales, in order to avoid spurious correlations. Results Communities were separated into five clusters reflecting their densities and taxonomic richness. They were significantly influenced by climatic conditions, soil texture and vegetation cover. Abundance and diversity, highest in tropical forests (1,895 ± 234 individuals/m 2 ) and savannahs (1,796 ± 72 individuals/m 2 ), progressively decreased in tropical cropping systems (tree‐associated crops, 1,358 ± 120 individuals/m 2 ; pastures, 1,178 ± 154 individuals/m 2 ; and annual crops, 867 ± 62 individuals/m 2 ), temperate grasslands (529 ± 60 individuals/m 2 ), forests (232 ± 20 individuals/m 2 ) and annual crops (231 ± 24 individuals/m 2 ) and temperate dry forests and shrubs (195 ± 11 individuals/m 2 ). Agricultural management decreased overall abundance by ≤54% in tropical areas and 64% in temperate areas. Connectivity varied with taxa, with dominant positive connections in litter transformers and negative connections with ecosystem engineers and Arachnida. Connectivity and modularity were higher in communities with low abundance and taxonomic richness. Main conclusions Soil macroinvertebrate communities respond to climatic, soil and land‐cover conditions. All taxa, except termites, are found everywhere, and communities from the five clusters cover a wide range of geographical and environmental conditions. Agricultural practices significantly decrease abundance, although the presence of tree components alleviates this effect.

Carotid Plaque Vulnerability Assessed by Combined Shear Wave Elastography and Ultrafast Doppler Compared to Histology - Guillaume Goudot; Jonas Sitruk; Anatole Jimenez; Pierre Julia; Lina Khider; Jean-Marc Alsac; Salma El Batti; Patrick Bruneval; Kisaki Amemyia; Olivier Pedreira; Hélène Mortelette; David Calvet; et al. (Translational Stroke Research, 2022)

Spruce budworm bacterial communities vary among sites and host tree species in a boreal landscape - Mathieu Landry; Patrick M. A. James; Dan Kneeshaw; Steven W. Kembel (Journal of Biogeography, 2022)
Aim Microbial communities often vary spatially in how they assemble and knowledge is lacking about which factors determine the biogeography of host‐associated microbiomes. Our aim is to assess the relative importance of spatial, environmental and host‐associated factors on microbial community composition of an important defoliating insect. Location Boreal forests in eastern Canada (Quebec, Newfoundland and Labrador). Taxon The eastern spruce budworm ( Choristoneura fumiferana ) and its associated bacterial communities. Methods We characterized bacterial communities associated with spruce budworm larvae using bacterial 16S rRNA gene amplicon sequencing. We quantified how much of the variation in these bacterial communities could be explained by (1) environmental conditions, (2) the microbiome of foliage the larvae were eating, (3) host tree species and (4) spatial structure as quantified using Moran's Eigenvector Maps (MEMs). Results Budworm larval microbiomes varied significantly among sites and between host tree species. Larvae bacterial community structure was strongly correlated with the structure of bacterial communities taken from paired foliage samples. Spatial structure, foliage bacterial communities and host tree species collectively explained almost one‐sixth of the variation in budworm bacterial communities while environmental conditions did not explain variation on their own. Main conclusions Lepidopteran microbiomes primarily originate from the foliage diet. However, subtle differences in microbial communities between larvae and foliage suggest that some bacteria establish and grow in the budworm microbiome, and that dispersal of bacteria from sources other than foliage as well as differences in environmental filtering between larval bodies and foliage play a role in the assembly of the budworm microbiome. While spatial location and spatial structure were also important drivers of spruce budworm bacterial community composition, none of the environmental variables we measured could explain the variation among sites, and identifying the drivers of this spatial variation remains an open question that will need to be addressed by future studies.

The Acid-Dependent and Independent Effects of Lactobacillus acidophilus CL1285, Lacticaseibacillus casei LBC80R, and Lacticaseibacillus rhamnosus CLR2 on Clostridioides difficile R20291 - Sathursha Gunaratnam; Carine Diarra; Patrick D. Paquette; Noam Ship; Mathieu Millette; Monique Lacroix (Probiotics and Antimicrobial Proteins, 2021)

The future for Mediterranean wetlands: 50 key issues and 50 important conservation research questions - Nigel G. Taylor; Patrick Grillas; Hazem Al Hreisha; Özge Balkız; Maud Borie; Olivier Boutron; Ana Catita; Jocelyn Champagnon; Semia Cherif; Kerim Çiçek; Luís T. Costa; Mohamed Dakki; et al. (Regional Environmental Change, 2021)

Muskox status, recent variation, and uncertain future - Christine Cuyler; Janice Rowell; Jan Adamczewski; Morgan Anderson; John Blake; Tord Bretten; Vincent Brodeur; Mitch Campbell; Sylvia L. Checkley; H. Dean Cluff; Steeve D. Côté; Tracy Davison; et al. (Ambio, 2020)

The global distribution and evolutionary history of the pT26‐2 archaeal plasmid family - Catherine Badel; Gaël Erauso; Annika L. Gomez; Ryan Catchpole; Mathieu Gonnet; Jacques Oberto; Patrick Forterre; Violette Da Cunha (Environmental Microbiology, 2019)
Summary Although plasmids play an important role in biological evolution, the number of plasmid families well‐characterized in terms of geographical distribution and evolution remains limited, especially in archaea. Here, we describe the first systematic study of an archaeal plasmid family, the pT26‐2 plasmid family. The in‐depth analysis of the distribution, biogeography and host–plasmid co‐evolution patterns of 26 integrated and 3 extrachromosomal plasmids of this plasmid family shows that they are widespread in Thermococcales and Methanococcales isolated from around the globe but are restricted to these two orders. All members of the family share seven core genes but employ different integration and replication strategies. Phylogenetic analysis of the core genes and CRISPR spacer distribution suggests that plasmids of the pT26‐2 family evolved with their hosts independently in Thermococcales and Methanococcales, despite these hosts exhibiting similar geographic distribution. Remarkably, core genes are conserved even in integrated plasmids that have lost replication genes and/or replication origins suggesting that they may be beneficial for their hosts. We hypothesize that the core proteins encode for a novel type of DNA/protein transfer mechanism, explaining the widespread oceanic distribution of the pT26‐2 plasmid family.

Contrasting resistance and resilience to extreme drought and late spring frost in five major European tree species - Yann Vitasse; Alessandra Bottero; Maxime Cailleret; Christof Bigler; Patrick Fonti; Arthur Gessler; Mathieu Lévesque; Brigitte Rohner; Pascale Weber; Andreas Rigling; Thomas Wohlgemuth (Global Change Biology, 2019)
Extreme climate events (ECEs) such as severe droughts, heat waves, and late spring frosts are rare but exert a paramount role in shaping tree species distributions. The frequency of such ECEs is expected to increase with climate warming, threatening the sustainability of temperate forests. Here, we analyzed 2,844 tree‐ring width series of five dominant European tree species from 104 Swiss sites ranging from 400 to 2,200 m a.s.l. for the period 1930–2016. We found that (a) the broadleaved oak and beech are sensitive to late frosts that strongly reduce current year growth; however, tree growth is highly resilient and fully recovers within 2 years; (b) radial growth of the conifers larch and spruce is strongly and enduringly reduced by spring droughts—these species are the least resistant and resilient to droughts; (c) oak, silver fir, and to a lower extent beech, show higher resistance and resilience to spring droughts and seem therefore better adapted to the future climate. Our results allow a robust comparison of the tree growth responses to drought and spring frost across large climatic gradients and provide striking evidence that the growth of some of the most abundant and economically important European tree species will be increasingly limited by climate warming. These results could serve for supporting species selection to maintain the sustainability of forest ecosystem services under the expected increase in ECEs.

Global mismatches in aboveground and belowground biodiversity - Erin K. Cameron; Inês S. Martins; Patrick Lavelle; Jérôme Mathieu; Leho Tedersoo; Mohammad Bahram; Felix Gottschall; Carlos A. Guerra; Jes Hines; Guillaume Patoine; Julia Siebert; Marten Winter; et al. (Conservation Biology, 2019)
Human activities are accelerating global biodiversity change and have resulted in severely threatened ecosystem services. A large proportion of terrestrial biodiversity is harbored by soil, but soil biodiversity has been omitted from many global biodiversity assessments and conservation actions, and understanding of global patterns of soil biodiversity remains limited. In particular, the extent to which hotspots and coldspots of aboveground and soil biodiversity overlap is not clear. We examined global patterns of these overlaps by mapping indices of aboveground (mammals, birds, amphibians, vascular plants) and soil (bacteria, fungi, macrofauna) biodiversity that we created using previously published data on species richness. Areas of mismatch between aboveground and soil biodiversity covered 27% of Earth's terrestrial surface. The temperate broadleaf and mixed forests biome had the highest proportion of grid cells with high aboveground biodiversity but low soil biodiversity, whereas the boreal and tundra biomes had intermediate soil biodiversity but low aboveground biodiversity. While more data on soil biodiversity are needed, both to cover geographic gaps and to include additional taxa, our results suggest that protecting aboveground biodiversity may not sufficiently reduce threats to soil biodiversity. Given the functional importance of soil biodiversity and the role of soils in human well‐being, soil biodiversity should be considered further in policy agendas and conservation actions by adapting management practices to sustain soil biodiversity and considering soil biodiversity when designing protected areas.

Biodiversity loss along a gradient of deforestation in Amazonian agricultural landscapes - Thibaud Decaëns; Marlúcia B. Martins; Alexander Feijoo; Johan Oszwald; Sylvain Dolédec; Jérôme Mathieu; Xavier Arnaud de Sartre; Diego Bonilla; George G. Brown; Yeimmy Andrea Cuellar Criollo; Florence Dubs; Ivaneide S. Furtado; et al. (Conservation Biology, 2018)
Assessing how much management of agricultural landscapes, in addition to protected areas, can offset biodiversity erosion in the tropics is a central issue for conservation that still requires cross‐taxonomic and landscape‐scale studies. We measured the effects of Amazonia deforestation and subsequent land‐use intensification in 6 agricultural areas (landscape scale), where we sampled plants and 4 animal groups (birds, earthworms, fruit flies, and moths). We assessed land‐use intensification with a synthetic index based on landscape metrics (total area and relative percentages of land uses, edge density, mean patch density and diversity, and fractal structures at 5 dates from 1990 to 2007). Species richness decreased consistently as agricultural intensification increased despite slight differences in the responses of sampled groups. Globally, in moderately deforested landscapes species richness was relatively stable, and there was a clear threshold in biodiversity loss midway along the intensification gradient, mainly linked to a drop in forest cover and quality. Our results suggest anthropogenic landscapes with high‐quality forest covering >40 % of the surface area may prevent biodiversity loss in Amazonia.

Xpert MTB/RIF diagnosis of childhood tuberculosis from sputum and stool samples in a high TB-HIV-prevalent setting - Patrick Orikiriza; Margaret Nansumba; Dan Nyehangane; Mathieu Bastard; Ivan Taremwa Mugisha; Denis Nansera; Juliet Mwanga-Amumpaire; Yap Boum; Elias Kumbakumba; Maryline Bonnet (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A Decision Support Tool Facilitating Medicine Design for Optimal Acceptability in The Older Population - Thibault Vallet; Emilie Belissa; Sandra Laribe-Caget; Alain Chevallier; François-Xavier Chedhomme; Patrick Leglise; Matthieu Piccoli; Hugues Michelon; Vanessa Bloch; Sylvie Meaume; Anne-Sophie Grancher; Nathalie Bachalat; et al. (Pharmaceutical Research, 2018)

Public Health Consequences of Lead in Drinking Water - Patrick Levallois; Prabjit Barn; Mathieu Valcke; Denis Gauvin; Tom Kosatsky (Current Environmental Health Reports, 2018)

Relation between Breast Cancer and High Glycemic Index or Glycemic Load: A Meta-analysis of Prospective Cohort Studies - Patrick Mullie; Alice Koechlin; Mathieu Boniol; Philippe Autier; Peter Boyle (Critical Reviews in Food Science and Nutrition, 2016)

PLGA-Based Nanoparticles: a Safe and Suitable Delivery Platform for Osteoarticular Pathologies - Mathieu Riffault; Jean-Luc Six; Patrick Netter; Pierre Gillet; Laurent Grossin (Pharmaceutical Research, 2015)

SYK is a target of lymphocyte-derived microparticles in the induction of apoptosis of human retinoblastoma cells - Qian Qiu; Chun Yang; Wei Xiong; Houda Tahiri; Mathieu Payeur; Rosanne Superstein; Anne-Sophie Carret; Patrick Hamel; Benjamin Ellezam; Bussières Martin; Mark Vezina; Przemyslaw Sapieha; et al. (Apoptosis, 2015)

Reassessment of the size of the Scopoli’s Shearwater population at its main breeding site resulted in a tenfold increase: implications for the species conservation - Pierre Defos du Rau; Karen Bourgeois; Mathieu Thévenet; Lise Ruffino; Sylvain Dromzée; Ridha Ouni; Awatef Abiadh; Roger Estève; Jean-Patrick Durand; Lorraine Anselme; Gilles Faggio; Jaber Mohamed Yahya; et al. (Journal of Ornithology, 2015)

A predictive model based on a pluviothermic index for leathery pocket and fruitlet core rot of pineapple cv. ‘Queen’ - Patrick Fournier; Aurore Benneveau; Christelle Hardy; Marc Chillet; Mathieu Léchaudel (European Journal of Plant Pathology, 2015)

Investigating the Neural Correlates of the Stroop Effect with Magnetoencephalography - Sophie Galer; Marc Op De Beeck; Charline Urbain; Mathieu Bourguignon; Noémie Ligot; Vincent Wens; Brice Marty; Patrick Van Bogaert; Philippe Peigneux; Xavier De Tiège (Brain Topography, 2015)

Inter- and Intra-Subject Variability of Neuromagnetic Resting State Networks - Vincent Wens; Mathieu Bourguignon; Serge Goldman; Brice Marty; Marc Op de Beeck; Catherine Clumeck; Alison Mary; Philippe Peigneux; Patrick Van Bogaert; Matthew J. Brookes; Xavier De Tiège (Brain Topography, 2014)

Chronic ingestion of cadmium and lead alters the bioavailability of essential and heavy metals, gene expression pathways and genotoxicity in mouse intestine - Jérôme Breton; Kelly Le Clère; Catherine Daniel; Mathieu Sauty; Lauren Nakab; Thierry Chassat; Joëlle Dewulf; Sylvie Penet; Christophe Carnoy; Patrick Thomas; Bruno Pot; Fabrice Nesslany; et al. (Archives of Toxicology, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Variation in adult body mass of roe deer: early environmental conditions influence early and late body growth of females - Mathieu Douhard; Jean-Michel Gaillard; Daniel Delorme; Gilles Capron; Patrick Duncan; François Klein; Christophe Bonenfant (Ecology, 2013)
There is increasing evidence that environmental conditions experienced early in life can markedly affect an organism's life history, but the pathways by which early environment influences adult phenotype are poorly known. We used long‐term data from two roe deer ( Capreolus capreolus ) populations (Chizé and Trois‐Fontaines, France) to investigate the direct and indirect (operating through fawn body mass) effects of environmental conditions during early life on adult body mass. We found that environmental conditions (population size and spring temperatures) around birth influenced body mass of adult females through both direct and indirect effects in both populations. The occurrence of direct effects means that, for a given fawn body mass, adult female mass decreases with adverse conditions in early life. In contrast, we found no evidence for direct effects of early‐life conditions on adult body mass of males, suggesting the existence of sex‐specific long‐term responses of body mass to stressful early conditions. Our results provide evidence that early environmental conditions influence the adult phenotype through persistent effects over the body development in wild mammal populations.

Impact of acamprosate on behavior and brain-derived neurotrophic factor: an open-label study in youth with fragile X syndrome - Craig A. Erickson; Logan K. Wink; Balmiki Ray; Maureen C. Early; Elizabeth Stiegelmeyer; Lauren Mathieu-Frasier; Vanessa Patrick; Debomoy K. Lahiri; Christopher J. McDougle (Psychopharmacology, 2013)

Comprehensive Functional Mapping Scheme for Non-Invasive Primary Sensorimotor Cortex Mapping - Mathieu Bourguignon; Veikko Jousmäki; Brice Marty; Vincent Wens; Marc Op de Beeck; Patrick Van Bogaert; Mustapha Nouali; Thierry Metens; Boris Lubicz; Florence Lefranc; Michael Bruneau; Olivier De Witte; et al. (Brain Topography, 2013)

Serum insulin and C-peptide concentration and breast cancer: a meta-analysis - Philippe Autier; Alice Koechlin; Mathieu Boniol; Patrick Mullie; Geremia Bolli; Julio Rosenstock; Peter Boyle (Cancer Causes & Control, 2013)

The effects of snowpack properties and plant strategies on litter decomposition during winter in subalpine meadows - Patrick Saccone; Samuel Morin; Florence Baptist; Jean-Marc Bonneville; Marie-Pascale Colace; Florent Domine; Mathieu Faure; Roberto Geremia; Jonathan Lochet; Franck Poly; Sandra Lavorel; Jean-Christophe Clément (Plant and Soil, 2013)

Using sets of behavioral biomarkers to assess short-term effects of pesticide: a study case with endosulfan on frog tadpoles - Mathieu Denoël; Bastien D’Hooghe; G. Francesco Ficetola; Catherine Brasseur; Edwin De Pauw; Jean-Pierre Thomé; Patrick Kestemont (Ecotoxicology, 2012)

Biological responses of maize (Zea mays) plants exposed to chlorobenzenes. Case study of monochloro-, 1,4-dichloro- and 1,2,4-trichloro-benzenes - Angélique San Miguel; Mathieu Faure; Patrick Ravanel; Muriel Raveton (Ecotoxicology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Right Hemisphere Recruitment During Language Processing in Frontotemporal Lobar Degeneration and Alzheimer’s Disease - Natalie Nelissen; Patrick Dupont; Mathieu Vandenbulcke; Thomas Tousseyn; Ronald Peeters; Rik Vandenberghe (Journal of Molecular Neuroscience, 2011)

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

The first fossil fungus gardens of Isoptera: oldest evidence of symbiotic termite fungiculture (Miocene, Chad basin) - Philippe Duringer; Mathieu Schuster; Jorge F. Genise; Andossa Likius; Hassan Taisso Mackaye; Patrick Vignaud; Michel Brunet (The Science of Nature, 2006)

Electrophysiological characterization of three non-synonymous single nucleotide polymorphisms (R87Q, A251T, and P307S) found in hKv1.5 - Isabelle Plante; Dominique Fournier; Guylaine Ricard; Benoît Drolet; Gilles O’Hara; Jean Champagne; Patrick Mathieu; Richard Baillot; Pascal Daleau (Pflügers Archiv - European Journal of Physiology, 2006)

Optimal first feed organism for South African mud crab Scylla serrata (Forskl) larvae - Jerome A. Davis; Mathieu Wille; Thomas Hecht; Patrick Sorgeloos (Aquaculture International, 2005)

A multi-scale study of soil macrofauna biodiversity in Amazonian pastures - Jrme Mathieu; Jean-Pierre Rossi; Michel Grimaldi; Philippe Mora; Patrick Lavelle; Corinne Rouland (Biology and Fertility of Soils, 2004)

Preface - Mathieu Wille; Patrick Sorgeloos (Aquaculture International, 2003)

Regulation of alternative oxidase gene expression in soybean - Ira Djajanegara; Patrick M. Finnegan; Christel Mathieu; Tulene McCabe; James Whelan; David A. Day (Plant Molecular Biology, 2002)

A bovine whole-genome radiation hybrid panel and outline map - John L. Williams; André Eggen; Luca Ferretti; Christine J. Farr; Mathieu Gautier; Giuseppe Amati; Glynn Ball; Tiziana Caramorr; Ricky Critcher; Sandro Costa; Patrick Hextall; David Hills; et al. (Mammalian Genome, 2002)